Solving container ship berthing problem using heuristics - Ahmad Nazri, Mohamad Zharfan Danial; Salleh Ahmad Bareduan, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study analyses total waiting, turnaround, penalty, and EstimatedTime Departure (ETD) of the last vessel leaving the berth to optimise vessel scheduling and berth allocation in port operations. The study compares First Come, First Serve (FCFS), Shortest Processing Time (SPT), and Longest Processing Time (LPT) heuristics for discrete and continuous berth allocation using past research data. The discrete case SPT heuristic has the lowest waiting time of 507.56 hours, turnaround time of 2422.56 hours, and penalty time of 165 hours. In the discrete case, FCFS regulates the final vessel's ETD best, with vessel Passat's earliest ETD observed on January 1, 2017, at 20:00. The comparison emphasises the importance of heuristic selection in berth allocation, requiring consideration of port characteristics, vessel categories, operational limitations, and specific goals for optimal performance.